Digital transformation, human resource competency, and adaptive leadership in public sector organizational performance - Irwan Irwan; Syawal Fahmi; Mohammad Aldilla Muntazar; Rita Paramawati; Septian Aryatama (Jurnal Indovisi, 2026)
This study aims to analyze the interrelationship between digital transformation, human resource competency, adaptive leadership, and organizational performance in public sector organizations. The findings reveal that sustainable organizational performance is not achieved through technological adoption alone but through the systemic integration of digital transformation, competent human resources, adaptive leadership, and organizational readiness. Among these factors, organizational readiness emerged as a critical moderating condition, shaping the effectiveness of digital transformation initiatives through institutional culture, governance structures, policy support, resource availability, and innovation capacity. Digital transformation provides technological infrastructure and governance modernization, while human resource competency supports effective implementation and operational performance. Adaptive leadership facilitates organizational flexibility, innovation, and responsiveness during transformation processes. This study contributes to the public sector management literature by proposing an integrated conceptual framework that explains organizational performance as a multidimensional outcome generated through the interaction of technological capability, human competency, leadership adaptability, and institutional preparedness. The framework offers strategic guidance for policymakers and public administrators in designing sustainable organizational transformation initiatives in the digital governance era.